PROBABILISTIC ZONING OF ADJACENT CATCHMENTS BY PHYSICAL MODELING - Yu. B. Andreev; A. N. Bozhinsky; N. A. Volodicheva; Zh. E. Molotkova; N. M. Molotkov (Лëд и снег, 2015)
Now the probabilistic zoning of avalanche sites is being made either on the basis of the available field data, or using the mathematical and physical modeling of avalanche dynamics processes. The work purpose consisted in research of interaction and compiling probabilistic zoning maps of two adjacent avalanche sites by a physical modeling method. For the two adjacent sites № 9 and 10 on the slope of northern exposition ofTchegetMountain(Elbrus region,Caucasus) the model of this slope with the scale of 1: 2 500 was created. The model dimension is 0,82 × 1,1 ×0,57 m. This model was produced using the 4-mm plywood sheets imposed against each other. The model horizontals correspond to the10 mnatural ones. The model slope was also surfaced by thin gypsum lay and then varnished. The fine-grained sawdust (0.1 mm) with a natural friction angle of 43º has been chosen as the loose material modeling snow. A series of experiments on modeling avalanche releases from the two sites were carried out resulted in the measurements of avalanche deposit parameters such as run-out distance and length, width and thickness of deposits. The similarity criteria were used during the experiments. The morphometric features of adjacent sites interaction are revealed. The basic result of the carried out work will consist in the probabilistic zoning map of two adjacent sites № 9 and 10.